INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN KETERAMPILAN MEMBACA ARAB - Toifah, Nur (UIN Maulana Malik Ibrahim Malang, 2019)
The current of globalization is fast entering the community, especially among teenagers. The influence of globalization on young people is so strong. This influence has demoralized and moral decadence experienced by students in Indonesia. Until now, the Indonesian nation is still faced with a number of problems, especially issues related to morals. To produce a superior generation, it is not unusual for a teacher to educate and instill morality that begins in the souls of students, this can be done by developing character education in the educational environment, namely by integrating character values in learning, including reading learning Arab. Integration of character education in Arabic reading learning is outlined in learning strategies, such as broken text and peer teaching learning strategies, in which the strategies are active, innovative, and fun. While the character values developed in Arabic reading learning are religious, honest, tolerance, independence, democratic, curiosity, communicative/friendly, social care, responsibility, discipline, caring for the environment and respecting achievement.